Pengadaan Awal Fasilitas Pemeliharaan dan Upaya Perolehan Filial 1 (F1) Ikan Zebra (Danio rerio) sebagai Hewan Laboratorium - Umul Karimah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Zebra fish (Danio rerio) is a laboratory animal that can be used for a wide field of research, testing, and education. Laboratories that wish to use Zebra Fish must have their own Zebra Fish rearing facility. The next step is to breed parental Zebra Fish from external sources until filial 1 (F1) is obtained in the facility which is then used later. This research is descriptive experimental, which describes the practical experience of providing maintenance, breeding, and rearing facilities for embryos and larvae. Quarantine specific facilities, number of tanks, water pH conditions, breeding methods, facility cleaning routines, and special larval feeds need to be considered for the success of early stage rearing facilities. This study showed that the embryo safety rate ranged from 38.2% to 88.9%. Meanwhile, for larvae up to the age of 21 dpf it ranged from 1.5%-9.1%, which indicated that the rearing conditions were still suboptimal, especially larval rearing. Facility procurement and maintenance costs are divided into mandatory and optional costs depending on the needs, location and time of the maintenance facility. Laboratories can independently design maintenance facilities that are effective to meet research needs and are cost efficient.